“En remuneración de sus servicios” en 1823-1856: El servicio doméstico en Chile a través de testamentos - Valenzuela, Pedro (European Review of Latin American and Caribbean Studies, 2024)
“In payment for its services” in 1823-1856: Domestic service in Chile through wills This article studies domestic service in Chile, particularly in the province of Concepción, during the first half of the nineteenth century. The main objective is to characterize the social and labour dynamics involved in domestic service during the first years of the Republic focusing on the study of the testamentary practices of the local elite evidenced through the review and analysis of wills notarized in the city of Concepción between 1823 and 1856. Methodologically, the selection of wills was carried out in a universe of 315 wills, 73 of which contained bequests to domestic service, and their analysis was carried out both quantitatively and qualitatively. The main conclusions are related to the characterization of the objects bequeathed and to the materialization or agency in the delivery of the bequests. Resumen El presente artículo estudia el servicio doméstico en Chile, particu-larmente en la provincia de Concepción, durante la primera mitad del siglo XIX. Se pretende caracterizar las dinámicas sociales y laborales que envuelven al servicio doméstico durante los primeros años de la República por medio del estudio de las prácticas testamentarias de la elite local, evidenciadas a través de la revisión y análisis de testamentos notariados en la ciudad de Concepción entre 1823 y 1856. Metodológicamente, la selección de testamentos se realizó en un universo de 315 testamentos, de los cuáles 73 contenían legados al servicio doméstico y su análisis se realizó tanto de manera cuantitativa como cualitativa. Las principales conclusiones se extraen en relación con la caracterización de los objetos legados y con la materialización u agencialidad en la entrega de los mismos.